UI/UX Design of Mobile Platform-Based Blood Donor Application Using User Centered Design Method - Tindi, Arifin Paulus; Lumasuge, Oktavianus; Sinsu, Noldy; Xaverius, Fransiskus (PT.KARYA GEMAH RIPAH, 2025)
Currently, there are many mobile-based blood donor applications available or various other platforms with the Indonesian Red Cross (PMI) as the center of the application, this is not in accordance with the situation in Sangihe Islands Regency where the blood transfusion process is still going directly to the hospital by searching for donors. through direct communication, via telephone, chat, or social media, for that, we need a UI/UX Design for a Mobile-Based Blood Donor Application in the form of an application prototype that adapts to the conditions and habits of users in the Sangihe Archipelago Regency. For this reason, it is necessary to design a mobile-based blood donor application that is right on target to be applied to users in Sangihe Islands Regency. This study aims to design a Mobile-Based Blood Donor Application with UI/UX Design in each stage of its manufacture involving users to get optimal results with the User Centered Design method.